Pengaruh Motivasi Belajar dan Lingkungan Teman Sebaya Terhadap Prestasi Belajar Matematika Siswa - Wike Revanaliza; Tasnim Rahmat; Rusdi Rusdi; Haida Fitri (Peneliti.net, 2023)
The purpose of this study was to determine the significant effect of learning motivation on mathematics learning achievement of 7th grade students of SMPN 7 Bukittinggi and to determine the significant effect of peer environment on mathematics learning achievement of 7th grade students of SMPN 7 Bukittinggi. The population of this study was 226 people and the sample was 34 people. The instruments used in this study were a learning motivation questionnaire and a peer environment questionnaire. The data analysis technique used is regression test. From the results of this study, the regression equation for learning motivation on learning achievement is Y = 4.88038462 + 0.44717308X1 with a correlation coefficient value of 0.60809407 which indicates a strong relationship strength and a determinant coefficient of 36.97%. Furthermore, from the regression significance test obtained > so, can be concluded that there is a significant influence of learning motivation on learning achievement in mathematics. Furthermore, from the peer environment regression equation on learning achievement, Y = 2.800158944+0.57757672 X2 with a correlation coefficient value of 0.45598425 which indicates a moderate relationship strength and a determinant coefficient of 20.79%. The results of the regression significance test, it was obtained that > so, can be concluded that there is a significant influence of peer environment on learning achievement in mathematic.